PENGEMBANGAN APLIKASI INFORMASI JADWAL PELAYANAN PENDETA BERBASIS ANDROID - Jenni Veronika Ginting (UPPM, 2017)
The development of this application is designed to make it easier for Churches, Pastors and Moderamen to see the pastor's ministry schedule in detail. With a large number of pastors scattered in the Moderamen service area both from Sabang to Merauke, which consists of Klasis and Runggun. The information application for android-based pastor GBKP service schedule is an application that can display a list of pastor services, a list of pastors 'names that are intended for all GBKP congregations to facilitate the dissemination of information on pastors' service schedules. Scheduling is very important for designing and managing a system consisting of a number of activities with limited resources.